Optical characterization of a polymer micro-optical light coupler for silicon channels - Ottevaere, Heidi; Van Overmeire, Sara; Albero, Jorge; Nieradko, Lukasz; Gorecki, Christophe; Thienpont, Hugo (Photonics Letters of Poland, 2012)
We present a micro-optical system for UV/VIS absorbance detection in silicon microfluidic channels, which consists of a micro-optical light coupler placed on top of the silicon fluidic channel to probe the molecules under test with laser light. We demonstrate the proof-of-concept of this microfluidic light probe by measuring standard samples of coumarin 102 dye with concentrations between 0.6µM and 6mM. Calibrating the system yields a detection limit of 4.3µM. To conclude we show that the concept of this microfluidic detection system is generic in that it can be applied at different positions on different microfluidic channel configurations. Full Text: PDF References G.M. Whitesides, "The origins and the future of microfluidics", Nature 442 (2006) 368-373.CrossRef A. Chandrasekaran, M. Packirisamy, Integrated Optical Microfluidic Lab-on-a-chip, Proc. of SPIE 7099 (2008) 70992B-1-8. CrossRef E. Verpoorte, A. Manz, H. Lüdi, A.E. Bruno, F. Maystre, B. Krattiger, H.M. Widmer, B.H. van der Schoot, N.F. de Rooij, A silicon flow cell for optical detection in miniaturized total chemical analysis systems, Sens. Act. B 6 (1992) 66-70.CrossRef R.M. Tiggelaar, T.T. Veenstra, R.G.P. Sanders, J.G.E. Gardeniers, M.C. Elwenspoek, A. van den Berg, "A light detection cell to be used in a micro analysis system for ammonia", Talanta 56 (2002) 331-339.CrossRef H. Salimi-Moosavi, Y. Jiang, L. Lester, G. McKinnon, D.J. Harrison, A multireflection cell for enhanced absorbance detection in microchip-based capillary electrophoresis devices, Electrophoresis 21 (2000) 1291-1299.CrossRef B. Ziaie, A. Baldi, M. Atashbar, Introduction to Micro/Nanofabrication, in: B. Bhushan (Ed.), Handbook of Nanotechnology, Springer, Berlin, 2007; pp 197-233.CrossRef C. Debaes, J. Van Erps, M. Vervaeke, B. Volckaerts, H. Ottevaere, V. Gomez, P. Vynck, L. Desmet, R. Krajewski, Y. Ishii, A. Hermanne, H. Thienpont, Deep Proton Writing: a rapid protoyping polymer microfabrication tool for micro-optical modules, New J. Phys. 8 (2006) 270-288.CrossRef C. Perrin, H. Fabre, D.L. Massart, Y. Vander Heyden, "Influence of peak measurement parameters on the quality of chiral electrophoretic separations", Electrophoresis 24 (2004) 2469-2480.CrossRef A. Felinger, Data analysis and signal processing in chromatography, Amsterdam, The Netherlands, Elsevier (1998) Y. Vander Heyden, R. Boqué Rodríguez, M. Cuesta, Calibration, LC-GC Europe 20 (2007).